Polymers for Fabricating Nerve Conduits - Shanfeng Wang; Lei Cai (International Journal of Polymer Science)
Peripheral nerve regeneration is a complicated and long-term medical challenge that requires suitable guides for bridging nerve injury gaps and restoring nerve functions. Many natural and synthetic polymers have been used to fabricate nerve conduits as well as luminal fillers for achieving desired nerve regenerative functions. It is important to understand the intrinsic properties of these polymers and techniques that have been used for fabricating nerve conduits. Previously extensive reviews have been focused on the biological functions and in vivo performance of polymeric nerve conduits. In this paper, we emphasize on the structures, thermal and mechanical properties of these naturally derived synthetic polymers, and their fabrication methods. These aspects are critical for the performance of fabricated nerve conduits. By learning from the existing candidates, we can advance the strategies for designing novel polymeric systems with better properties for nerve regeneration.